2021
DOI: 10.1093/brain/awab279
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré syndrome after SARS-CoV-2 infection in an international prospective cohort study

Abstract: In the wake of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, an increasing number of patients with neurological disorders, including Guillain-Barré syndrome (GBS), have been reported following this infection. It remains unclear, however, if these cases are coincidental or not, as most publications were case reports or small regional retrospective cohort studies. The International GBS Outcome Study is an ongoing prospective observational cohort study enrolling patients with GBS with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 44 publications
(52 reference statements)
1
37
1
2
Order By: Relevance
“…About 70% of cases of GBS are preceded by an infectious respiratory or gastrointestinal illness [ 23 ]. Twenty-two percent of the GBS patients included in the prospective International GBS Outcome Study during the first four months of the Covid-19 pandemic had a preceding SARS-CoV-2 infection, and data indicate this to be due to a post-infectious disease mechanism rather than direct viral invasion [ 24 ]. In CIDP, however, there is paucity as well as heterogeneity of data on preceding infections, with these implicated in approximately 10–20% [ 15 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…About 70% of cases of GBS are preceded by an infectious respiratory or gastrointestinal illness [ 23 ]. Twenty-two percent of the GBS patients included in the prospective International GBS Outcome Study during the first four months of the Covid-19 pandemic had a preceding SARS-CoV-2 infection, and data indicate this to be due to a post-infectious disease mechanism rather than direct viral invasion [ 24 ]. In CIDP, however, there is paucity as well as heterogeneity of data on preceding infections, with these implicated in approximately 10–20% [ 15 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it was initially thought that the pandemic would trigger a spike in GBS cases, data has shown otherwise. Instead, three studies found either stable incidence or a decline in GBS cases during the SARS-CoV-2 era ( Keddie et al, 2021 ; Luijten et al, 2021 ; Umapathi et al, 2021 ). As with other novel viral pathogens, like Zika, there is an incontrovertible and emerging, albeit small, body of evidence that suggests a temporal link between COVID-19 infection and GBS ( Aladawi et al, 2022 ).…”
Section: Neurological Manifestation In Covid-19 Patientsmentioning
confidence: 99%
“…110 A higher prevalence of COVID-19 was noted among GBS cases when compared to the general population, but this could have been secondary to substantial recruitment bias. 110…”
Section: Guillain-barré Syndromementioning
confidence: 93%